PENGEMBANGAN SUMBER DAYA MANUSIA UNTUK MENINGKATKAN KUALITAS PENDIDIKAN DI AL WAFI ISLAMIC BOARDING SCHOOL DEPOK, JAWA BARAT - Aditya, Viedy Dimas (Institut Daarul Qur'an Jakarta, Indonesia, 2023)
The purpose of this study is to explain: (1) Pesantren Al Wafi Islamic Boarding School strategy to improve human resource competence in accordance with Education Quality Standards; (2) The effect of HR Organization development on work culture at Pesantren Al Wafi Islamic Boarding School; and (3) Future perspectives for HR Organization development. This study used qualitative phenomenological methodology. Data collection methods through observation, documentation, and interviews. Research results: (1) The HR competency development strategy of Pesantren Al Wafi includes the HR development planning process, competency development programs and activities, factors that support and hinder competency development. (2) The influence of HR organization development on work culture at Pesantren Al Wafi has shown the results of knowledge, which is in the form of increasing employee understanding of what is meant by